Organizational Culture Impact in Enhancing Job Performance A Case Study in the Modern Paint Industries Company - هادي, عفاف حسن; محمود, ياسر عادل (Journal of Economics and Administrative Sciences, 2014)
The organizational culture is considered as an important topic. In this research, this topic was studied in modern paints Industries Company to assess its role in job performance and to show if there is this relationship between them or no. it is, also, attempted to measure this strength of this relationship if any. The 40 cases research sample was chosen. This sample included the chief executive, his assistants, key managers, and their assistants. The questioner consists of two sets of questions : the first set ( concerning the organizational culture) covers six variables (Physical structures , Symbols , Values , Beliefs , Expectations , and Rites & Rituals ) , the second set covers the job performance which could be concluded from six indicators (Job Satisfaction, The absence of workers, Quality, Productivity, Time, Creativity ). After statistical analysis it has been shown that there is a strong positive relationship between organizational culture and job performance. It has been shown, also, that the organizational culture has positive effect on job performance .It is recommended that the company: must take into consideration and well recognize the topic of organizational culture, make use of this topic in raising the level of job performance .